2021
DOI: 10.3389/fimmu.2020.592080
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Signaling Promotes Glioma Progression Through Stabilizing Sox9

Abstract: Gliomas are brain and spinal cord malignancies characterized by high malignancy, high recurrence and poor prognosis, the underlying mechanisms of which remain largely elusive. Here, we found that the Sry-related high mobility group box (Sox) family transcription factor, Sox9, was upregulated and correlated with poor prognosis of clinical gliomas. Sox9 promotes migration and invasion of glioma cells and in vivo development of xenograft tumors from inoculated glioma cells. Sox9 functions downstream of the transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
(38 reference statements)
0
21
0
1
Order By: Relevance
“…The related mechanism and therapeutic strategies have been gradually clarified. It has already been found that the high proliferation and invasion of gliomas and the poor prognosis in glioma patients are usually accompanied by SMAD signaling in early studies, and Sox9 becomes an important regulatory target when TGF-β works in glioma progression [ 212 , 213 ]. TGF-β plays an essential role in glioma progression by inducing the proliferation, invasion, EMT, and migration of glioma cells and depressing immune effector cells [ 214 216 ].…”
Section: Introductionmentioning
confidence: 99%
“…The related mechanism and therapeutic strategies have been gradually clarified. It has already been found that the high proliferation and invasion of gliomas and the poor prognosis in glioma patients are usually accompanied by SMAD signaling in early studies, and Sox9 becomes an important regulatory target when TGF-β works in glioma progression [ 212 , 213 ]. TGF-β plays an essential role in glioma progression by inducing the proliferation, invasion, EMT, and migration of glioma cells and depressing immune effector cells [ 214 216 ].…”
Section: Introductionmentioning
confidence: 99%
“…8D). A tendency towards enhanced β-catenin and SMAD2/3 activity, known mediators of stem cell maintenance and proliferation following TMZ treatment (21), was detected in shPPP2R5E tumors, whereas expression of SOX9, a protein involved in differentiation, migration and invasion of GBM (22), was reduced (Fig. 8D).…”
Section: Resultsmentioning
confidence: 98%
“…Ultimately, this model highlights that the presence of human stem cell derived microglial cells with human glioma cells results in not only larger tumors but also an upregulation of genes similar to those known to be upregulated in certain gliomas ( 40 45 ). Recent findings have begun to shed light on how GBM can use microglia to induce immunosuppression within the tumor microenvironment.…”
Section: Cell Lines and Mouse Models Of Gliomamentioning
confidence: 92%